2005
DOI: 10.1111/j.1742-4658.2005.04860.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signalling by nicotinic acid adenine dinucleotide phosphate (NAADP)

Abstract: Intracellular Ca2+ signals are coordinated to elicit spatiotemporal patterns. These include repetitive Ca 2+ transients, which may be localized or propagated as regenerative waves that may also pass into neighbouring cells [1][2][3]. d-myo-Inositol 1,4,5-trisphosphate (InsP 3 ) is a well-established intracellular Ca 2+ mobilizing messenger in many cell types [3], and is a paradigm for additional molecules that release Ca 2+ from intracellular Ca 2+ stores. Cyclic ADP-ribose (cADPR) and nicotinic acid adenine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 77 publications
1
39
0
1
Order By: Relevance
“…Both plant and animal cells have been shown to respond to application of NAADP (reviewed in refs. [12][13][14]. A limited number of reports demonstrated that extracellular stimulation increased intracellular NAADP concentrations, being in accordance with a second messenger function for NAADP (reviewed in refs.…”
mentioning
confidence: 80%
“…Both plant and animal cells have been shown to respond to application of NAADP (reviewed in refs. [12][13][14]. A limited number of reports demonstrated that extracellular stimulation increased intracellular NAADP concentrations, being in accordance with a second messenger function for NAADP (reviewed in refs.…”
mentioning
confidence: 80%
“…Nicotinic acid adenine dinucleotide phosphate (NAADP) 2 is a newly discovered Ca 2ϩ messenger with unique properties that has been extensively investigated in various tissues and cell lines (3)(4)(5)(6)(7)(8). Cardiac tissue expresses high affinity binding sites for NAADP, and NAADP stimulates Ca 2ϩ efflux from microsomal fractions derived from rat heart (9).…”
mentioning
confidence: 99%
“…cADPR is produced by plasma membrane-bound ADPR cyclase at relatively neutral physiological pH. NAADP, on the other hand, is primarily generated at very low pH such as that found in lysosomal and endo/exocytic vesicles (16,41). Whereas NAADP may be generated by nonenzymatic means, the ADPR cyclase from the A. californica and the mammalian ADPR cyclase CD38 are the only enzymes currently known to produce NAADP (19,25).…”
mentioning
confidence: 99%